2016
DOI: 10.1002/jbm.b.33648
|View full text |Cite
|
Sign up to set email alerts
|

Polymer degradation and drug delivery in PLGA‐based drug–polymer applications: A review of experiments and theories

Abstract: Poly (lactic-co-glycolic acid) (PLGA) copolymers have been broadly used in controlled drug release applications. Because these polymers are biodegradable, they provide an attractive option for drug delivery vehicles. There are a variety of material, processing, and physiological factors that impact the degradation rates of PLGA polymers and concurrent drug release kinetics. This work is intended to provide a comprehensive and collective review of the physicochemical and physiological factors that dictate the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
244
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 318 publications
(266 citation statements)
references
References 160 publications
(426 reference statements)
5
244
0
Order By: Relevance
“…Several authors have demonstrated that the presence of drugs in PLGA-based DDSs influences the rate of matrix degradation. [44] Giunchedi et al showed a 27% increase in vitro of LA and GA monomers when diazepam was encapsulated into PLGA microspheres, compared to empty ones. [142] These results may be attributed to different functional groups of the drug that could react with carboxyl end groups of PLGA, accelerating the degradation process by autocatalysis.…”
Section: Drug Release From Poly(lactic-co-glycolic) Acid Delivery Sysmentioning
confidence: 99%
See 2 more Smart Citations
“…Several authors have demonstrated that the presence of drugs in PLGA-based DDSs influences the rate of matrix degradation. [44] Giunchedi et al showed a 27% increase in vitro of LA and GA monomers when diazepam was encapsulated into PLGA microspheres, compared to empty ones. [142] These results may be attributed to different functional groups of the drug that could react with carboxyl end groups of PLGA, accelerating the degradation process by autocatalysis.…”
Section: Drug Release From Poly(lactic-co-glycolic) Acid Delivery Sysmentioning
confidence: 99%
“…Adapted with permission. [44] increases the degradation rate of the polymer. [17] Despite the enrolment of enzymes in this process is still not clear, some authors believe that they are able to speed up PLGA degradation.…”
Section: Physical-chemical Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, PLGA is approved by the United States Food and Drug Administration (FDA) for clinical use in human beings, 37 and a lot of drug regents based on PLGA delivery system come forth for the treatment of various diseases. 38 This study further clarified that PLGA is compatible with AuNP-mediated siRNA delivery, particularly in the field of dental implantation. Furthermore, the strategy proposed is of favorable biocompatibility, easy to manipulate, and of controllable biodegradation rate.…”
Section: Plga-based Mirna Delivery System In Implant Functionalizationmentioning
confidence: 64%
“…One of the assumptions implicit in the preceding models is that the matrix material does not swell or degrade in vivo. However, many device applications employ materials that swell (Peppas, Hilt, Khademhosseini, & Langer, 2006) and/or degrade (Xu, Kim, Saylor, & Koo, 2017) by design. In these scenarios, one must consider not only transport of the leachable, but also the rate and extent of swelling as well as the change in properties as the material degrades.…”
Section: Future Opportunitiesmentioning
confidence: 99%